Analytical platform for conducting Arduino online courses. - Султангазина, Наргиза (Вестник ЗКУ, 2022)
The relevance of studying online courses is due to their active introduction into the education system and the possibilities of their use to implement the concept of lifelong learning. Against the backdrop of the formation of e-pedagogics as a branch of pedagogical science, the theoretical and pedagogical analysis of online courses as an educational resource is of great research interest and determines the purpose of this study. The authors made analyzes of online courses and platforms.In this article, training courses on Arduino on modern platforms (YouTube, Instagram, Telegram, Udemy) were considered with different presentation of information about the basic functions of Arduino, the possibility of developing a microcontroller and online learning, and the advantages and disadvantages of these platforms were identified. The Instagram platform is used mostly as advertising accounts for selling online courses and does not have an educational function, although there are tools for implementing Arduino online courses and reaching a larger audience.